PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SDI CIKAL HARAPAN - Sari, Mahsya Novita; Izhari, Fadhilah; Maswanto, Maswanto (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2024)
This study was conducted with the aim of testing and analyzing the effect of work motivation, work environment, and job satisfaction on teacher performance at Cikal Harapan Islamic Elementry School. Many factors affect teacher performance. However, the authors limit the problem to three variables, namely Work Motivation, Work Environment, and Job Satisfaction.The sampling technique in this study used saturated samples or non-probability sampling and data collection was carried out by distributing questionnaires to teachers of Cikal Harapan Islamic Elementary School.The data analysis methods used in this study include validity test, reliability test, classical assumption test, multiple linear analysis and coefficient of determination (R2) analysis to test and prove the hypothesis.The results of this study indicate that work motivation has a significant effect on teacher performance at Cikal Harapan Islamic Elementary School with the results of t count> t table, namely 4.925> 2.01954 and a significant value of 0.000 <0.005. The work environment has a significant effect on teacher performance at Cikal Harapan Islamic School with the results of t count> t table, namely 2.286> 2.01954 and a significant value of 0.027 <0.05. Job satisfaction has no significant effect on teacher performance at Cikal Harapan Islamic Elementary School with the results of t count smaller than t table, namely 0.712 < 2.01954 and a significant value of 0.481> 0.05 and based on the f test (together) the results of f count> f table are 45.443> 2.83 and significant at 0.000 < 0.05.